(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
As soon as the revolt began, the Mewatis without losing any time, actively participated in the revolt. But the Mewati had to fight simultaneously on three fronts. On the first front, they had to fight against the British army and police on the second front, they had to fight against the British loyalists such as the Khanzadas of Nuh, the Rajput of Hathin and hondsi, the Rawat jats of Hotel and the Kayasth of Sahna and on the third front, they had to fight against the Army of the British loyalists states such as Alwar, Bharatpur and Jaipur. The Mewat area of Haryana specially became the centre of struggle against these forces. The brave Mewatis fought and defeated all these powers. They, not only, removed the tyrannical rule of East India Company from the Mewat area of Haryana, but also, the grip of the East India Company became loose, to some extent, in the Mewat areas which were under Alwar and Bharatpur States.